We real cool : Black men and masculinity - hooks, bell, 1952-2021 (Routledge, 2004)
Bell hooks' brilliant and controversial new book We Real Cool: Black Men and Masculinity goes beyond the usual analysis of the black to ask questions which other books are unwilling to address.